The Effectiveness of Self-Compassion Training to Increase the Resilience of Wives Who Have Drug-Addicted Husbands in The District Area Of Aur Medan Maimun - Untario*, Evelyn; Martono, Anggitha Faradiba; Giawa, Theodora Ananda; Tambunan, Clara Elizabeth; Elvinawanty, Rianda; Syamantha, Arbana (Universitas Syiah Kuala, 2023)
The primary aim of this study is to evaluate the effectiveness of self-compassion training in enhancing the resilience of wives who have husbands struggling with drug addiction in the Aur Medan region. The proposed hypothesis in this research suggests that a substantial distinction exists in the levels of resilience among wives with drug-addicted husbands before and after undergoing self-compassion training. The hypothesis posits that the resilience of these wives will witness an increase after the self-compassion training. Employing a pre-experimental design with a one-group pretest-posttest setup, the collected data was subjected to the Shapiro-Wilk normality test, with data being considered normally distributed when the resultant significance value is p 0.05. Analysis of the pretest data produces a p-value coefficient of 0.969 (p 0.05), and the posttest data yields a p-value coefficient of 0.094 (p 0.05), indicating conformity to normal distribution. The research methodology adopts a quantitative approach, employing the paired sample T-Test analysis technique with the support of SPSS (Statistical Product and Service Solution) version 26. The criteria from the paired sample T-Test resulted in a significance value of 0.000. A value of Sig.0.05 entails the endorsement of the hypothesis, signifying that self-compassion indeed contributes to the augmentation of resilience. Thus, it can be concluded that the levels of resilience increase after the engagement in self-compassion training, as compared to the period preceding the training.